Cardiorespiratory profiling during simulated lunar mission using impedance pneumography. (May 2019) - Młyńczak, Marcel; Kołodziejczyk, Agata; Krysztofiak, Hubert; Ambroszkiewicz, Grzegorz; Żyliński, Marek; Cybulski, Gerard
Graphical abstract: Highlights: Lunares Analog Research Station allows testing under space-like conditions. Astronauardiorespiratory data were obtained under those conditions for the first time, using Pneumonitor 2. The results were compared with normative values collected from elite athletes. Respiration added to cardiac data would provide better monitoring and evaluation. Cardiorespiratory profile can be used to plan the schedule of the mission. Abstract: Manned spaceflight requires research in diverse areas, including neuropsychology and human physiology. For these subjects, the Lunares Analog Research Station was established in Pila, Poland. It allows testing of crew members under space-like conditions. One experiment, Lunar Expedition I, was performed on a group of 6 analogue astronauts over 14 days. All were studied for their subjective perception of time and also asked to carry out mission-specific activities, like digging or repairing a rover during an extravehicular activity (EVA). The aims of the study were to measure cardiorespiratory signals using ECG and impedance pneumography devices under those conditions; to evaluate the quality of the data and the level of motion artefacts; and to assess the subjects' status and adaptation. We used our own prototype, Pneumonitor 2, that enables registering respiratory-related impedance curve, a single-lead ECG and 3-axis accelerometer signals. Due to problems with a detachment of electrodes, we ultimately collected 10 full registrations from 5 astronauts. All signals were pre-processed and annotated. The set of cardiorespiratory parameters, including heart and respiratory activity indicators, was calculated for 3 main states: at rest, doing squats and performing various activities during EVA. We compared the results with normative values collected from elite athletes. The considered parameters were found to be in the normal range, typically slightly worse than the average for the athletes. The physiological responses are in line with expectations. Impedance pneumography enables to measure quantitative parameters of breathing like tidal volume and may be used during dynamic conditions. Combined with the ECG signal provides an objective astronaut's cardiorespiratory profile. One can use it to assess the adaptation and to plan the schedule of the mission. However, there is a need for development of a wearable electronic textile solution for the target electrodes, to deal with sweating occurring while wearing a three-layer EVA suit.